2014
DOI: 10.1097/fpc.0000000000000036
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of methotrexate pharmacogenomics in rheumatoid arthritis shows multiple novel risk variants and leads for TYMS regulation

Abstract: In this first ever genome-wide analysis on MTX treatment response in RA patients, 10 new risk loci were identified. These preliminary findings warrant replication in independent studies. Further, TYMS expression at the post-transcriptional level seems to be probably regulated through an antisense-RNA involving the 6-bp ins/del marker in the overlapping segment at 3'UTR of TYMS-ENOSF1, a finding with impending pharmacogenetic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 49 publications
1
41
0
Order By: Relevance
“…Pharmacogenomics is also an important area of work of many scientists (Senapati et al. ). However, the contribution of Indian scientists to gene mapping has been limited.…”
Section: Researchmentioning
confidence: 99%
“…Pharmacogenomics is also an important area of work of many scientists (Senapati et al. ). However, the contribution of Indian scientists to gene mapping has been limited.…”
Section: Researchmentioning
confidence: 99%
“…Alleles influencing response only to specific drugs would also be expected, for example, those involved in the drug's metabolism. However, no clinically useful alleles have yet been identified, with genome-wide association studies identifying only a handful of non-replicated loci for response to methotrexate (MTX)4 and tumour necrosis factor inhibitors (TNFi) 5–7. For HLA-DRB1 , the main risk locus for developing RA, most studies report no association of the ‘shared epitope’ alleles with response to MTX8–10 or TNFi,8 11–14 but a recent study found that alleles altering several amino acids in HLA-DRB1 were associated with radiological progression and response to TNFi 15…”
Section: Introductionmentioning
confidence: 99%
“…39 There is a chance that future individualization of therapy will allow to adapt the applied treatment to a particular molecular subtype of a disease and the patient's genotype. The further development of pharmacogenetics will contribute to improved efficacy of therapies…”
mentioning
confidence: 99%